From phytoaccumulation to post-harvest use of water fern for landfill management. (1st November 2016) - Song, Uhram; Kim, Dae Won; Waldman, Bruce; Lee, Eun Ju
Abstract: We examined the potential of Azolla japonica as a remediating plant for leachate channels and post-accumulation use as fertilizer for landfill slope. The harvested biomass of Azolla after one month grown in leachate was 254% that of the initial biomass and the predicted annual harvestable biomass of Azolla using a growth model was 32 times that of the initial biomass. Na, Fe, Mn, Mg, and P were accumulated in Azolla at very high concentrations. Such rapid increase of biomass and high accumulation rates suggest that this plant could be an excellent remediating plant. The post-harvest use of Azolla as compost was studied for the management and use of phytoaccumulating Azolla . Metal contents of Azolla compost were below permissible limits for co-composting material. Nitrogen, organic matter, P, and Mg content of the Azolla compost improved the soil condition of the landfill and enhanced ecophysiological responses of the plants. The application of Azolla compost can improve management of sanitary landfills, including the restoration of vegetation. Considering its ease of harvesting, high accumulation rates, harvestable biomass and suitability for composting, Azolla can provide a suitable solution for sustainable management of leachate channels and landfill slopes. Highlights: We examined remediation ability and post-harvest use of water fern ( Azolla japonica ). Azolla japonica showed high remediation ability and rapid biomass increase. Azolla japonica compost improved soil condition and performance of plants. Azolla japonica can provide a sustainable solution for phytoremediation.